2008
DOI: 10.1113/expphysiol.2007.041145
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal programming of skeletal development in sheep is mediated by somatotrophic axis function

Abstract: Nutritional and metabolic exposure during critical periods of prenatal and neonatal development in animals and humans may induce long-term effects on health status in later life. The aim of this study was to investigate the effects of neonatal treatment with β-hydroxy-β-methylbutyrate (HMB) during the first 3 weeks of life on programming of skeletal development in sheep. The study was performed on 12 male sheep divided into two groups. While the control group was treated with placebo, the lambs in the HMB grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…It has been demonstrated that prenatal administration of HMB has a positive impact on the growth and development of farm animals (26,27). Until now there were no analyses concerning the influence of a prenatal administration of the HMB to pregnant dams on the morphology and functioning of the brains of their offspring.…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…It has been demonstrated that prenatal administration of HMB has a positive impact on the growth and development of farm animals (26,27). Until now there were no analyses concerning the influence of a prenatal administration of the HMB to pregnant dams on the morphology and functioning of the brains of their offspring.…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…Urine can be obtained using a special external urine collector (Windhagen et al 2002) or collected by cystocentesis (Allen et al 2000). Urine and serum samples should be stored at -20°C for mineral analyses (Chanetsa et al 2000, Taylor et al 2009, Sousa et al 2014a) and at -80°C until determination of BTMs (Seebeck et al 2005, Tatara 2008, Sousa et al 2014b, which provides molecular stability for several months (Lomeo and Bolner 2000).…”
Section: Sample and Storagementioning
confidence: 99%
“…Sheep are a common animal model used to study the relationship of regulatory processes of systemic growth and development with physiological, metabolic and nutritional factors, both in prenatal and postnatal life (Masters et al 1993;Blum and Hammon 2000;Kwon et al 2003;Tatara 2008). However, little is known about physiological changes in plasma free amino acid concentrations as well as their relationships during postnatal life and after the development of the forestomach.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results correspond with other studies concerning BCAA (Shimomura et al 2004). In studies on turkeys and pigs, where dietary alteration of amino acid metabolism was induced, plasma concentrations of valine, leucine and isoleucine were altered analogously in response to the applied nutritional manipulations (Tatara et al 2006(Tatara et al , 2008Tatara 2009). The balance between BCAA and aromatic amino acids such as phenylala-nine and tyrosine is known as Fischer's ratio, and is routinely utilised as an important diagnostic marker for monitoring health status and for studying the progression of liver diseases which influence amino acid metabolism (Noguchi et al 2008).…”
Section: Discussionmentioning
confidence: 99%